Magiczność słowa we wczesnoindyjskiej refleksji nad jezykiem - Lipnicki, Michał (Investigationes Linguisticae, 2010)
The present paper aims to present the notion of language emerging from the ideas from the early, prephilosophical phase of the development of Indian thought. We start our investigation with the analysis of two Rigvedic hymns (circa 1600 BC). Then we proceed to some excerpts from Brahmanas texts (circa 1000 BC) and finally we end our inquiry with the analysis of selected parts of the Upanishads (circa 700 BC – 200 CE).